DIFFERENT WAYS OF CALCULATING CATCHMENT RAINFALL: CASES IN INDONESIA - F. Balany (Journal of the Civil Engineering Forum, 2011)
Uncertainty in obtaining average catchment rainfall remains a basic question to which commonly (almost) nobody has any attention in the design of waterworks. Little attention is given to the influence of the applied method on the final design values. Applying Thiessen polygon for almost every effort of obtaining catchment average is still questionable since there are two other methods which are also often used. Up to now, there is no reliable information to which method is the best among the three most commonly applied methods. This study explores the behavior of the three methods of obtaining catchment rainfall, which are mean arithmetic, Thiessen polygon and isohyetal method. The accuracy is obtained by comparing the calculated design values computed by Unit Hydrograph and those obtained by frequency analysis of recorded discharge. The result says that no methods consistently superior.